Necessity of Proper Lashing of Containers on the Ship's Deck as Part of Optimization of the Sea Voyage - Radišić, Zoran (Promet - Traffic&Transportation, 2004)
These days we are witnessing an increase of container trafficin general and at sea in particular. In order to economizetheir business the ship owners are building bigger container vesselswhich can carry up to 8000 TEUs (Maersk line) and otherbig carriers are following suit. On the drawing board is the vesselof 12000 TEUs from the mentioned ship owner. Obviously,such large quantity of containers requires highly efficient lashingequipment in order to secure them, particularly thosestowed on the deck Under the deck, almost as a rule all contemporarycontainer ships have cell guides as securing devices.Attention in this work is focused on container lashing systemexposed on the ship's deck and the relevant forces acting on thelash system during transportation at sea. Once containers areloaded on the ship's deck they should be safely secured by oneof the lashing systems in order to prevent damage and that is theprincipal task of the lashing equipment engaged within theframe of the lash system. In order to fulfill its objective theforces acting on the container should be properly calculated.The acting forces, their influence and the way of calculatingthem have been explained for all the major ship movementsand suggestions for optimum lashing equipment are given.